The roles and functions of atrocity-related United Nations commissions of inquiry in the international legal order : navigating between principle and pragmatism - Harwood, Catherine, 1985- (Leiden: Brill Nijhoff, 2020)
"The plight of the Rohingya people in Myanmar has been documented in manifold reports alleging escalating atrocities.1 Accompanying these allegations were mounting calls for an international investigation under the auspices of the United Nations. After several years of diplomatic wrangling, in 2017 the United Nations Human Rights Council (hrc) established "an independent international fact- finding mission ... to establish the facts and circumstances of the alleged recent human rights violations by military and security forces, and abuses, in Myanmar, in particular in Rakhine State ... with a view to ensuring full accountability for perpetrators and justice for victims""--
Charting the Rise of UN Atrocity-Related Inquiry -- Establishing the Mandate : Mandating Authorities as Architects of Atrocity-Related Inquiries -- Mandate Interpretation and Implementation : Commissions as Engineers of Their Roles and Functions -- Identification of the Applicable Legal Framework -- Law-Application in the Inquiry Context -- Translating Violations to Responsibility Regimes in an 'Era of Accountability'.
Based on author's thesis (doctoral - Rijksuniversiteit te Leiden, 2018) issued under title: Navigating between principle and pragmatism : the roles and functions of atrocity-related United Nations commissions of inquiry in the international legal order.
Includes bibliographical references (pages 329-389) and index.
Keywords: Criminal investigation (International law); Political atrocities; International commissions of inquiry; War crimes investigation; Rohingya (Burmese people) -- Crimes against -- Burma